Challenges, Opportunities, and the Future of the Blue Economy in Indonesia - Poppy Wulandari; Puja Afwanda Mayako; Mutiara Cahyaningrum (PT. Altaf Publishing Corp, 2025)
Indonesia, the world's largest archipelagic country with vast maritime territory, holds significant potential for developing a blue economy that promotes sustainable growth through effective marine resource management. Key sectors such as fisheries, maritime tourism, and marine renewable energy are essential to national economic development. However, the blue economy's progress faces challenges, including ecosystem degradation, maritime pollution, and sectoral fragmentation. This study identifies the main challenges and explores opportunities in sustainable fisheries, maritime ecotourism, and marine renewable energy. Using a descriptive-analytical approach with qualitative and quantitative analysis of secondary data, the findings reveal that Indonesia's blue economy remains highly promising, especially with policies supporting sustainability, human resource development, and eco-friendly technologies. The novelty of this research lies in its cross-sectoral synthesis, which emphasizes the need for convergence between environmental governance and maritime economic policy.